ANALISA PENGARUH PERSEPSI HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA E- COMMERCE SHOPEE DI PEKANBARU - Sartika, Dewi; Mulyana, Sri; Sofyan, Deviana (Jurnal Ekonomi Bisnis Kompetif, 2025)
This study aims to analyze the influence of price perception and promotion on purchasing decision on the shopee E-commerce platform in Pekanbaru. The proliferation of e-commerce platforms has profoundly reshaped consumer purchasing behavior, offering unprecedented convenience, product diversity, reliability assurances, competitive pricing, and compelling promotional incentives. Consequently, consumers are increasingly inclined towards online shopping experiences. However, within this dynamic digital marketplace, intense price competition and a multitude of sophisticated promotional strategies emerge as pivotal determinants significantly influencing consumer purchasing decisions. This research employed a quantitative approach, with data gathered via questionnaires administered to respondents who made purchases on the Shopee e-commerce platform in Pekanbaru. The collected data were analyzed using multiple linear regression to examine the influence of price perception, promotion, and purchasing decisions. The research findings indicate that price perception significantly influences purchasing decisions on Shopee e-commerce in Pekanbaru. This finding stands in stark contrast to promotions, which showed no significant influence on purchasing decisions. This indicates that consumers' perception of a product's price (whether it is considered expensive, affordable, or commensurate with its quality) is a primary determinant in their purchasing decisions